Mysterious travelers : Steve Ditko and the search for a new liberal identity - Kruse, Zack (Great comics artists., 2021)
"Steve Ditko (1927-2018) is one of the most important contributors to American comic books. As the cocreator of Spider-Man and sole creator of Doctor Strange, Ditko made an indelible mark on American popular culture. Mysterious Travelers: Steve Ditko and the Search for a New Liberal Identity resets the conversation about his heady and powerful work. Always inward facing, Ditko's narratives employed superhero and supernatural fantasy in the service of self-examination, and with characters like the Question, Mr. A, and Static, Ditko turned ordinary superhero comics into philosophic treatises. Many of Ditko's philosophy-driven comics show a clear debt to ideas found in Ayn Rand's Objectivism. Unfortunately, readers often reduce Ditko's work to a mouthpiece for Rand's vision. Mysterious Travelers unsettles this notion. In this book, Zack Kruse argues that Ditko's philosophy draws on a complicated network of ideas that is best understood as mystic liberalism. Although Ditko is not the originator of mystic liberalism, his comics provide a unique window into how such an ideology operates in popular media. Examining selections of Ditko's output from 1953 to 1986, Kruse demonstrates how Ditko's comics provide insight into a unique strand of American thought that has had a lasting impact"--